Izbrani razvojni in okoljevarstveni problemi slovenskega podeželja z vidika sonaravnega razvoja - Lampič, Barbara (Geographica Slovenica, 2000)
Inspite of different development of the predominant activites, which are influencing the economic, social, morphological, etc. image of the Slovene cuntryside, agriculture is still the decisive factor influencing the cultural image of Slovene countryside. In comparison to the level of development of agriculture in the European Union Member States, agriculture of our country is indication numerous deficiencies in structure and productivity of the agricultural production, however looking from the environmental point of view, basic pressures on individual environmental components are lower. Therefore negative landscape effects of agriculture remain spatialy limited mostly on gravel plains and part of tertiary hilly areas.
Keywords: agrarna geografija; podeželje; rural area; kmetijstvo; agriculture; ecology; ekologija; environmental protection; varstvo okolja; raba tal; onesnaževanje okolja; ekološko ravnotežje; sonaravni razvoj; Slovenia; Slovenija